Invisibility - Cremer, Andrea R.; Levithan, David (New York : Philomel Books, 2013)
"To break his curse of invisibility, a boy is helped by a girl, who is the only one who can see him"--
Keywords: Magic -- Fiction; Charms -- Fiction; Friendship -- Fiction; Family problems -- Fiction